2012
DOI: 10.1002/pi.4270
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of carbon nanotubes in polypropylene melt

Abstract: The correlation between shear stress and the orientation of single‐walled carbon nanotubes (SWCNTs) in an SWCNT/polypropylene composite during the melt process was investigated. Highly oriented composite fibers were produced by extruding the polypropylene melt using a capillary rheometer. The experimental range of shear rates covered those of common polymer melt‐shaping processes. The effect of functionalization of the SWCNTs on orientation was also investigated. Polarized Raman spectroscopy was used to analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…a‐SWCNT or a‐SWCNT/MMT composite shows higher H m 1 than that of p‐SWCNT or p‐SWCNT/MMT composite, respectively. The increasing difference of H m 1 between p‐ and a‐SWCNT composites with increasing shear stress is related to the higher orientation of a‐SWCNTs at higher shear stress . This idea can be applied to SWCNT/MMT composites.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…a‐SWCNT or a‐SWCNT/MMT composite shows higher H m 1 than that of p‐SWCNT or p‐SWCNT/MMT composite, respectively. The increasing difference of H m 1 between p‐ and a‐SWCNT composites with increasing shear stress is related to the higher orientation of a‐SWCNTs at higher shear stress . This idea can be applied to SWCNT/MMT composites.…”
Section: Resultsmentioning
confidence: 97%
“…However, the tensile properties and Young's modulus of the composite were unaffected by the addition of 1 wt% SWCNTs. Orientation of CNTs was strongly dependent on the elasticity of the polymer and the experienced shear stress . Recently, the orientation of CNTs in the polymer melt was reported, and it was found to be strongly dependent on the shear stress experienced during melt processing .…”
Section: Introductionmentioning
confidence: 99%
“…Polarized Raman spectroscopy is a powerful tool for investigating the orientation of CNTs in a polymer matrix by the analysis of intensity variation of the G-band with the variation of angle between the CNT axis and polarization direction of the incident light. The composite with random MWCNTs was isotropous, so the variation of the angle between axis of oriented CNTs and laser source could not cause a change in the intensity of the composite material spectrum [16,[21][22][23][24]. However, for the composite with oriented CNTs, it would lead to a significant change in the absorption strength of each characteristic peak.…”
Section: Polarized Raman Characterizationmentioning
confidence: 99%
“…As a result, surface modification of BaTiO 3 by organic phases that are miscible with PEN is adopted. Mechanical stretching is another common method to improve performance, especially the mechanical properties of PEN. We have reported that the tensile strength was increased 110% when a film of PEN was hot‐stretched by 100% …”
Section: Introductionmentioning
confidence: 99%